Peningkatan Penelitian Berkualitas Melalui Pelatihan Keterampilan Menulis Karya Ilmiah Bagi Dosen dan Mahasiswa - Luluh Abdillah Kurniawan; Ika Widiastuti (Jurnal Pengabdian Kepada Masyarakat, 2024)
The background to the problem of written work in Indonesia is that the quality of research is not yet high due to the large amount of plagiarism and research jockeying. Researchers are required to always prioritize originality of ideas, be able to use research supporting tools and master skills that support research activities. Therefore, research skills training is needed. The aim of this training is so that lecturers and researchers can have the ability to maximize applications to support scientific writing. This activity is aimed at lecturers and students with the aim of assisting in writing scientific articles to be published in international journals. The results of this activity are the ability to apply Mendeley software, avoid plagiarism using Paraphrase and using the Grammarly application. This activity was carried out in the form of training via the zoom application and Whatsapp Group as a means of supporting information